Conductive graphite slurry as well as preparation method and application thereof

By performing micro-oxidation and nano-treating treatment on graphite, combined with high shear homogenizer and high-pressure microjet treatment technology, conductive graphite pastes with excellent conductivity and good dispersion are prepared, which solves the problem of insufficient conductivity and dispersion of graphite pastes in the prior art.

CN119581095APending Publication Date: 2025-03-07INST OF URBAN ENVIRONMENT CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411954598.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The prior art has challenges in improving the conductivity and dispersion of graphite slurries, especially in terms of dispersion, bonding and adhesion of nanographite in water, it is difficult to achieve uniform connection and efficient and stable dispersion.

Method used

The graphite is treated by micro-oxidation and nano-nification strategies to form micro-oxidized conductive graphite, and a conductive graphite paste with excellent conductivity and good dispersion is prepared through high shear homogenizer and high-voltage microjet treatment technology.

Benefits of technology

It significantly improves the conductivity and dispersion of graphite slurry, realizes the stable and dense adhesion of nanographite insulating pore walls, and breaks through key technical bottlenecks such as long-term, efficient and stable dispersion and stable adhesion of pore walls.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005215562900000151
    Figure BDA0005215562900000151
  • Figure BDA0005215562900000161
    Figure BDA0005215562900000161
Patent Text Reader

Abstract

The invention provides conductive graphite slurry as well as a preparation method and application thereof, and the preparation method comprises the following steps: performing micro-oxidation treatment on graphite to obtain micro-oxidized conductive graphite; mixing the micro-oxidized conductive graphite, a solvent and a dispersing agent, and performing dispersion treatment to obtain micro-oxidized conductive graphite slurry; and performing nanocrystallization treatment on the micro-oxidized conductive graphite slurry to obtain the conductive graphite slurry. According to the preparation method, micro-oxidation and nanocrystallization strategies are utilized, so that the compatibility of graphite and other materials is remarkably enhanced, and the conductivity and dispersity of the graphite slurry are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of conductive materials, in particular to conductive slurry, and in particular to a conductive graphite slurry and a preparation method and application thereof. Background Art

[0002] As communication electronic equipment continues to be miniaturized and portable, the integration of flexible printed circuit boards is getting higher and higher, and the aperture and diameter-to-depth ratio of the holes that play a role in interlayer conduction are getting smaller and smaller. The traditional chemical copper plating hole metallization process has been difficult to adapt to the requirements of technological development. The direct electroplating technology of holes is being adopted by more and more flexible printed circuit board manufacturers, including metal palladium conductive film method, polymer conductive film method and black hole method. Among them, the black hole method is the most widely used, and its main advantages are low cost and less pollution. The raw material of the black hole method is mainly carbon black, with low production cost, fewer types of chemical reagents used and non-toxic and harmless, easy sewage treatment and low cost, simple process flow, high production efficiency, and is a green and advanced production and manufacturing technology.

[0003] With the continuous development and improvement of this technology, the carbon black conductive matrix has been gradually replaced by graphite, forming a new generation of metallization reagent - black shadow. Compared with carbon black, graphite has a thin flaky crystal structure and the property of electron energy transfer in a two-dimensional plane. After forming a film on the pore wall, it can give small pores and deep pores better conductivity, and at the same time obtain a thinner conductive layer network. However, the technology of graphite matrix black shadow reagent faces many difficulties and challenges. The black shadow reagent requires that the nanographite has excellent dispersion in water, strong bonding and adhesion with the pore wall, good uniformity of interconnection between graphite sheets, and excellent conductivity of the metallized pore film layer. Therefore, how to improve the conductivity and dispersibility of graphite slurry has become a hot spot in current technical research.

[0004] CN104562115A discloses a black pore liquid for printed circuit boards with graphite particles as a conductive matrix. A water-soluble polymer and a corresponding poor solvent are added to the black pore liquid. Under the induction of the corresponding poor solvent, the water-soluble polymer takes the graphite particles as precipitation nuclei and condenses in the water phase. The aqueous polymer chains are attached to the surfaces of the graphite particles by physical bonds and coated around the graphite particles to form a black pore liquid with hydrophilic polymer-coated graphite particles. The steric hindrance and electrostatic repulsion of the long-chain polymer on the particle surface are utilized to greatly enhance the dispersion stability of the black pore liquid.

[0005] CN108323036A discloses a black hole liquid and a black hole process, wherein the disclosed black hole liquid includes 2%-4% conductive agent, 5%-9% dispersant, 4%-7% surfactant, 1%-2% potassium carbonate, and 78%-88% deionized water. The black hole liquid is stabilized by adding a surfactant accounting for 4%-7% to the black hole liquid, which affects the conductive properties of graphite.

[0006] The existing technology usually increases the steric hindrance or repulsion between graphite particles through additives to achieve the purpose of graphite separation and improve the dispersibility of graphite slurry, and additives usually account for a large proportion.

[0007] Therefore, it is of great significance to develop a preparation method for stabilizing graphite slurry by changing the surface properties of graphite itself. Summary of the invention

[0008] In view of the shortcomings of the prior art, the present invention aims to provide a conductive graphite slurry and a preparation method and application thereof. The present invention uses micro-oxidation and nano-crystallization strategies to give inert graphite excellent electronegativity, promote efficient dispersion of graphite in water, enhance the compatibility of graphite with other materials, and improve the conductivity and dispersibility of graphite slurry.

[0009] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a method for preparing a conductive graphite slurry, the preparation method comprising:

[0011] The graphite is micro-oxidized to obtain micro-oxidized conductive graphite; the micro-oxidized conductive graphite, a solvent and a dispersant are mixed and dispersed to obtain micro-oxidized conductive graphite slurry; the micro-oxidized conductive graphite slurry is nano-treated to obtain the conductive graphite slurry.

[0012] The present invention uses micro-oxidation and nano-crystallization strategies to give inert graphite excellent electronegativity, promote efficient dispersion of graphite in water, enhance the compatibility of graphite with other materials, and improve the conductivity and dispersibility of graphite slurry.

[0013] Preferably, the micro-oxidation treatment comprises mixing the graphite with an oxidant solution and heating the mixture for reaction.

[0014] Preferably, the oxidant solution includes an oxidant, and the mass fraction of the oxidant is 0.3%-1%, for example, it can be 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%, including but not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0015] In the present invention, the oxidant forms oxygen-containing groups such as hydroxyl, carboxyl, and carbonyl groups by oxidizing carbon atoms at the edge of the graphite layer, thereby achieving micro-oxidation of the graphite. If the concentration of the oxidant is too high, the structure of the graphite is damaged, resulting in a significant decrease in the conductivity and other properties of the graphite. If the concentration of the oxidant is too low, the degree of graphite oxidation is insufficient, which is not conducive to maintaining the liquid phase dispersibility and high conductivity of the graphite.

[0016] Preferably, the oxidant comprises any one of peracetic acid, ammonium sulfate, potassium persulfide or sodium percarbonate, or a combination of at least two thereof. Typical but non-limiting combinations include peracetic acid and ammonium sulfate, potassium persulfide and sodium percarbonate, ammonium sulfate and potassium persulfide, or sodium percarbonate and peracetic acid.

[0017] Preferably, the mass volume ratio of the graphite to the oxidant solution is 0.5Kg / L-5Kg / L, for example, it can be 0.5Kg / L, 1Kg / L, 1.5Kg / L, 2Kg / L, 2.5Kg / L, 3Kg / L, 3.5Kg / L, 4Kg / L, 4.5Kg / L or 5Kg / L, including but not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0018] Preferably, the temperature of the heating reaction is 120°C-180°C, for example, it can be 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C, 175°C or 180°C, including but not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0019] Preferably, the heating reaction time is 6h-48h, for example, it can be 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, 24h, 26h, 28h, 30h, 32h, 34h, 36h, 38h, 40h, 42h, 44h, 46h or 48h, including but not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0020] The present invention does not particularly limit the method of the heating reaction. For example, the heating reaction can be carried out in a high-pressure reactor.

[0021] Preferably, the solvent comprises an organic solvent and / or water.

[0022] Preferably, the organic solvent comprises any one of N-methylpyrrolidone, N,N-dimethylformamide or ethanol or a combination of at least two thereof, and typical but non-limiting combinations include N-methylpyrrolidone and N,N-dimethylformamide, N-methylpyrrolidone and ethanol or N,N-dimethylformamide and ethanol.

[0023] Preferably, the dispersant includes any one of sodium dodecylbenzene sulfonate, polyvinyl alcohol, polyvinyl pyrrolidone, hydroxymethyl cellulose, polypropylene pyrrolidone or hydroxypropyl cellulose, or a combination of at least two thereof. Typical but non-limiting combinations include sodium dodecylbenzene sulfonate and polyvinyl alcohol, polyvinyl pyrrolidone and hydroxymethyl cellulose, polypropylene pyrrolidone and hydroxypropyl cellulose, polyvinyl alcohol and polyvinyl pyrrolidone, hydroxymethyl cellulose and polypropylene pyrrolidone, or hydroxypropyl cellulose and sodium dodecylbenzene sulfonate.

[0024] Preferably, the mass ratio of the micro-oxidized conductive graphite, the organic solvent and the dispersant is (900-1100):(2500-5500):(15-25), for example, it can be 900:2500:15, 920:3000:16, 940:3250:17, 960:3500:18, 980:3750:19, 1000:4000:20, 1020:4250:21, 1040:4500:22, 1060:4750:23, 1080:5000:24 or 1100:5500:25, including but not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0025] Preferably, the method of mixing the slightly oxidized conductive graphite, the organic solvent and the dispersant comprises stirring.

[0026] Preferably, the stirring speed is 950rpm-1050rpm, for example, it can be 950rpm, 960rpm, 970rpm, 980rpm, 990rpm, 1000rpm, 1010rpm, 1020rpm, 1030rpm, 1040rpm or 1050rpm, including but not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0027] Preferably, the stirring time is 2 h-6 h, for example, 2 h, 3 h, 4 h, 5 h or 6 h, including but not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0028] Preferably, the dispersion process is carried out in a high shear homogenizing mixer.

[0029] In the present invention, a high shear homogenizing mixer is used for dispersion treatment to obtain a slightly oxidized conductive graphite slurry, which has a better dispersion effect and reduces the particle size of the slightly oxidized conductive graphite, thereby improving the dispersibility and conductivity of the graphite.

[0030] Preferably, the flow range of the high shear homogenizer is 0.2 m 3 / h-1.5m 3 / h, for example, it can be 0.2m3 / h、0.3m 3 / h、0.4m 3 / h、0.5m 3 / h、0.6m 3 / h、0.7m 3 / h、0.8m 3 / h、0.9m 3 / h、1m 3 / h、1.1m 3 / h、1.2m 3 / h、1.3m 3 / h、1.4m 3 / h or 1.5m 3 / h, including but not limited to the listed values, and other values ​​not listed in the numerical range are also applicable.

[0031] Preferably, the rotation speed of the high shear homogenizer is 2000rpm-3500rpm, for example, it can be 2000rpm, 2200rpm, 2400rpm, 2600rpm, 2800rpm, 3000rpm, 3200rpm, 3400rpm or 3500rpm, including but not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0032] Preferably, the nano-processing method includes high-pressure microfluidization processing.

[0033] In the present invention, the micro-oxidized conductive graphite slurry is subjected to high-pressure micro-jet treatment, which can make the slurry particle size distribution uniform without destroying the slurry properties, and the particle size of the slurry after treatment can reach the nanometer range.

[0034] Preferably, the working pressure of the high-pressure microfluidization treatment is 120MPa-150MPa, for example, it can be 120MPa, 122MPa, 124MPa, 126MPa, 128MPa, 130MPa, 132MPa, 134MPa, 136MPa, 138MPa, 140MPa, 142MPa, 144MPa, 146MPa, 148MPa or 150MPa, including but not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0035] Preferably, the flow rate of the high-pressure microfluidization treatment is 100L / h-200L / h, for example, it can be 100L / h, 110L / h, 120L / h, 130L / h, 140L / h, 150L / h, 160L / h, 170L / h, 180L / h, 190L / h or 200L / h, including but not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0036] Preferably, the operating temperature of the high-pressure microfluidization treatment is 60°C-70°C, for example, it can be 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C or 70°C, including but not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0037] Preferably, the number of high-pressure microfluidization treatments is 8-12 times, for example, 8 times, 9 times, 10 times, 11 times or 12 times, including but not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0038] Preferably, after the nano-treatment, the average particle size of graphite in the conductive graphite slurry is 200nm-1000nm, for example, it can be 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, 750nm, 800nm, 850nm, 900nm, 950nm or 1000nm, including but not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0039] In a second aspect, the present invention provides a conductive graphite slurry, which is prepared by the preparation method described in the first aspect.

[0040] In a third aspect, the present invention provides an application of the conductive graphite slurry as described in the second aspect, wherein the conductive graphite slurry is applied in the fields of batteries, supercapacitors, sensors or conductive coatings.

[0041] The micro-oxidized nano-conductive graphite slurry provided by the present invention has wide application potential in the fields of batteries, supercapacitors, etc. Its excellent conductivity and good dispersibility make it have important application value in high-performance electronic devices.

[0042] When the conductive graphite slurry prepared by the present invention is applied to conductive coatings, stable and dense adhesion of nanographite to insulating pore walls can be achieved, breaking through key technical bottlenecks such as long-term, efficient and stable dispersion of nanographite and firm adhesion to pore walls.

[0043] Compared with the prior art, the present invention has the following beneficial effects:

[0044] (1) The present invention utilizes micro-oxidation and nano-sizing strategies to endow inert graphite with excellent electronegativity, effectively improve the surface properties of graphite, promote efficient dispersion of graphite in water, enhance the compatibility of graphite with other materials, and improve the conductivity and dispersibility of graphite slurry.

[0045] (2) The conductive graphite slurry prepared by the present invention has wide application potential in the fields of batteries, supercapacitors and conductive coatings. When applied to conductive coatings, it can achieve stable and dense adhesion of nanographite on the insulating pore walls, breaking through key technical bottlenecks such as long-term, efficient and stable dispersion of nanographite and stable adhesion of pore walls. DETAILED DESCRIPTION

[0046] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0047] In order to clearly illustrate the technical solution of the present invention, in a specific embodiment, the graphite particle size in the raw material can be 1 μm-10 μm. The above description is only for the purpose of clearly illustrating the technical solution of the present invention and is not regarded as a further limitation of the present invention.

[0048] Example 1

[0049] This embodiment provides a method for preparing a conductive graphite slurry, the preparation method comprising:

[0050] Put graphite and 0.5% peracetic acid solution into a high-pressure reactor, the mass volume ratio of graphite powder to peracetic acid solution is 2kg / L, heat to 150°C, and react for 12 hours. After the high-pressure reactor is cooled to room temperature, filter the solid-liquid mixture in the reactor, and dry the solid to obtain slightly oxidized conductive graphite.

[0051] Micro-oxidized conductive graphite, N-methylpyrrolidone and sodium dodecylbenzene sulfonate were mixed in a mass ratio of 950:3500:20 by stirring at a speed of 950 rpm for 2 h. After the mixing was completed, the mixture was added to a high shear homogenizer for homogenization at a flow rate of 1.5 m 3 / h, the rotation speed is 2000rpm, and a uniform and highly dispersed micro-oxidized conductive graphite slurry is obtained.

[0052] The slightly oxidized conductive graphite slurry was subjected to high-pressure microfluidization treatment 10 times, with a working pressure of 130 MPa, a flow rate of 100 L / h, and a working temperature of 65° C. to obtain a conductive graphite slurry.

[0053] The average particle size of the nanographite in the conductive graphite slurry prepared in this embodiment is 500 nm.

[0054] Example 2

[0055] This embodiment provides a method for preparing a conductive graphite slurry, the preparation method comprising:

[0056] Put graphite and 0.3% peracetic acid solution into a high-pressure reactor, the mass volume ratio of graphite powder to peracetic acid solution is 5kg / L, heat to 120°C, and react for 48 hours. After the high-pressure reactor is cooled to room temperature, filter the solid-liquid mixture in the reactor, and dry the solid to obtain the slightly oxidized conductive graphite.

[0057] The micro-oxidized conductive graphite, N,N-dimethylformamide and sodium dodecylbenzene sulfonate were mixed in a mass ratio of 900:2500:15 by stirring at a speed of 1050 rpm for 2 h. After the mixing and stirring, the mixture was added to a high shear homogenizer for homogenization at a flow rate of 0.5 m 3 / h, the rotation speed is 3500rpm, and a slightly oxidized conductive graphite slurry is obtained.

[0058] The slightly oxidized conductive graphite slurry was subjected to high-pressure microfluidization treatment 8 times, with a working pressure of 150 MPa, a flow rate of 150 L / h, and a working temperature of 65° C. to obtain a conductive graphite slurry.

[0059] The particle size of the nanographite in the conductive graphite slurry prepared in this embodiment is about 740 nm.

[0060] Example 3

[0061] This embodiment provides a method for preparing a conductive graphite slurry, the preparation method comprising:

[0062] Put graphite and 0.8% ammonium sulfate solution into a high-pressure reactor, the ratio of graphite powder to peracetic acid solution is 0.5kg / L, heat to 180°C, and react for 8 hours. After the high-pressure reactor is cooled to room temperature, filter the solid-liquid mixture in the reactor, and dry the solid to obtain the slightly oxidized conductive graphite.

[0063] The micro-oxidized conductive graphite, N-methylpyrrolidone and polyvinylpyrrolidone were mixed in a mass ratio of 1100:5500:25 by stirring at a speed of 1000 rpm for 5 h. After the mixing was completed, the mixture was added to a high shear homogenizer for homogenization at a flow rate of 1 m 3 / h, the rotation speed is 2000rpm, and a slightly oxidized conductive graphite slurry is obtained.

[0064] The slightly oxidized conductive graphite slurry was subjected to high-pressure microfluidization treatment 12 times, with a working pressure of 120 MPa, a flow rate of 180 L / h, and a working temperature of 70° C. to obtain a conductive graphite slurry.

[0065] The average particle size of the nanographite in the conductive graphite slurry prepared in this embodiment is 330 μm.

[0066] Example 4

[0067] This embodiment provides a method for preparing a conductive graphite slurry. The preparation method is the same as that of Embodiment 1 except that the mass fraction of the oxidant in the oxidant solution is 0.1%.

[0068] The average particle size of the nanographite in the conductive graphite slurry prepared in this embodiment is 550 nm.

[0069] Example 5

[0070] This embodiment provides a method for preparing a conductive graphite slurry. The preparation method is the same as that of Embodiment 1 except that the mass fraction of the oxidant in the oxidant solution is 2%.

[0071] The average particle size of the nanographite in the conductive graphite slurry prepared in this embodiment is 540 nm.

[0072] Example 6

[0073] This embodiment provides a method for preparing a conductive graphite slurry. The preparation method is the same as that of Embodiment 1 except that the heating reaction temperature is 100°C.

[0074] The average particle size of the nanographite in the conductive graphite slurry prepared in this embodiment is 533 nm.

[0075] Example 7

[0076] This embodiment provides a method for preparing a conductive graphite slurry. The preparation method is the same as that of Embodiment 1 except that the heating reaction temperature is 200°C.

[0077] The average particle size of the nanographite in the conductive graphite slurry prepared in this embodiment is 545 nm.

[0078] Example 8

[0079] This embodiment provides a method for preparing a conductive graphite slurry. The method includes: 3 / h, the rest are the same as in Example 1.

[0080] The average particle size of the nanographite in the conductive graphite slurry prepared in this embodiment is 535 nm.

[0081] Example 9

[0082] This embodiment provides a method for preparing a conductive graphite slurry. The method includes: 3 / h, the rest are the same as in Example 1.

[0083] The average particle size of the nanographite in the conductive graphite slurry prepared in this embodiment is 505 nm.

[0084] Example 10

[0085] This embodiment provides a method for preparing a conductive graphite slurry. The preparation method is the same as that of Embodiment 1 except that the rotation speed of the high shear homogenizer is 1000 rpm.

[0086] The average particle size of the nanographite in the conductive graphite slurry prepared in this embodiment is 510 nm.

[0087] Embodiment 11

[0088] This embodiment provides a method for preparing a conductive graphite slurry. The preparation method is the same as that of Embodiment 1 except that the rotation speed of the high shear homogenizer is 4000 rpm.

[0089] The average particle size of the nanographite in the conductive graphite slurry prepared in this embodiment is 490 nm.

[0090] Example 12

[0091] This embodiment provides a method for preparing a conductive graphite slurry. The preparation method is the same as that of Embodiment 1 except that the working pressure of the high-pressure microfluidization treatment is 100 MPa.

[0092] The average particle size of the nanographite in the conductive graphite slurry prepared in this embodiment is 508 nm.

[0093] Embodiment 13

[0094] This embodiment provides a method for preparing a conductive graphite slurry. The preparation method is the same as that of Embodiment 1 except that the working pressure of the high-pressure microfluidization treatment is 170 MPa.

[0095] The average particle size of the nanographite in the conductive graphite slurry prepared in this embodiment is 498 nm.

[0096] Embodiment 14

[0097] This embodiment provides a method for preparing a conductive graphite slurry. The preparation method is the same as that of Embodiment 1 except that the flow rate of the high-pressure microfluidization treatment is 80 L / h.

[0098] The average particle size of the nanographite in the conductive graphite slurry prepared in this embodiment is 502 nm.

[0099] Embodiment 15

[0100] This embodiment provides a method for preparing a conductive graphite slurry. The preparation method is the same as that of Embodiment 1 except that the flow rate of the high-pressure microfluidization treatment is 220 L / h.

[0101] The average particle size of the nanographite in the conductive graphite slurry prepared in this embodiment is 505 nm.

[0102] Example 16

[0103] This embodiment provides a method for preparing a conductive graphite slurry. The preparation method is the same as that of Embodiment 1 except that the working temperature of the high-pressure microfluidization treatment is 45° C.

[0104] The average particle size of the nanographite in the conductive graphite slurry prepared in this embodiment is 503 nm.

[0105] Embodiment 17

[0106] This embodiment provides a method for preparing a conductive graphite slurry. The preparation method is the same as that of Embodiment 1 except that the working temperature of the high-pressure microfluidization treatment is 85° C.

[0107] The average particle size of the nanographite in the conductive graphite slurry prepared in this embodiment is 501 nm.

[0108] Embodiment 18

[0109] This embodiment provides a method for preparing a conductive graphite slurry. The preparation method is the same as that of Embodiment 1 except that the number of high-pressure microfluidization treatments is 6.

[0110] The average particle size of the nanographite in the conductive graphite slurry prepared in this embodiment is 536 nm.

[0111] Embodiment 19

[0112] This embodiment provides a method for preparing a conductive graphite slurry. The preparation method is the same as that of Embodiment 1 except that the number of high-pressure microfluidization treatments is 15.

[0113] The average particle size of the nanographite in the conductive graphite slurry prepared in this embodiment is 423 nm.

[0114] Comparative Example 1

[0115] This comparative example provides a method for preparing a conductive graphite slurry, the preparation method comprising:

[0116] Graphite, N-methylpyrrolidone and sodium dodecylbenzene sulfonate were mixed and stirred in a mass ratio of 1: (120-140): (30-50), the mixing speed was 950 rpm, and the mixing time was 2 h. After the mixing was completed, they were added into a high shear homogenizer for homogenization, the mixer flow rate was 1.5 m3 / h, and the speed was 2000 rpm to obtain a uniform and highly dispersed mixed graphite slurry.

[0117] The mixed graphite slurry was subjected to high-pressure microfluidization treatment 10 times, with a working pressure of 100 MPa, a flow rate of 100 L / h, and a working temperature of 65° C. to obtain a conductive graphite slurry.

[0118] The average particle size of the nanographite in the conductive graphite slurry prepared in this comparative example is 578 nm.

[0119] Comparative Example 2

[0120] This comparative example provides a method for preparing a conductive graphite slurry, the preparation method comprising:

[0121] Put graphite and 0.5% peracetic acid solution into a high-pressure reactor, the mass volume ratio of graphite powder to peracetic acid solution is 2kg / L, heat to 150°C, and react for 12 hours. After the high-pressure reactor is cooled to room temperature, filter the solid-liquid mixture in the reactor, and dry the solid to obtain slightly oxidized conductive graphite.

[0122] Micro-oxidized conductive graphite, N-methylpyrrolidone and sodium dodecylbenzene sulfonate are mixed and stirred in a mass ratio of 1: (120-140): (30-50), the mixing and stirring speed is 950 rpm, the mixing and stirring time is 2 h, and after the mixing and stirring is completed, high-pressure microfluidization treatment is performed 10 times, the working pressure is 100 MPa, the flow rate is 100 L / h, and the working temperature is 65 ° C to obtain a conductive graphite slurry.

[0123] The average particle size of the nanographite in the conductive graphite slurry prepared in this comparative example is 569 nm.

[0124] Comparative Example 3

[0125] This comparative example provides a method for preparing a conductive graphite slurry, the preparation method comprising:

[0126] Put graphite and 0.5% peracetic acid solution into a high-pressure reactor, the mass volume ratio of graphite powder to peracetic acid solution is 2kg / L, heat to 150°C, and react for 12 hours. After the high-pressure reactor is cooled to room temperature, filter the solid-liquid mixture in the reactor, and dry the solid to obtain slightly oxidized conductive graphite.

[0127] The micro-oxidized conductive graphite, N-methylpyrrolidone and sodium dodecylbenzene sulfonate were mixed and stirred in a mass ratio of 1: (120-140): (30-50) at a mixing speed of 950 rpm for 2 h. After the mixing and stirring, the mixture was added into a high shear homogenizer for homogenization at a mixer flow rate of 1.5 m 3 / h, the rotation speed is 2000rpm, and a conductive graphite slurry is obtained.

[0128] The average particle size of the nanographite in the conductive graphite slurry prepared in this comparative example is 2000 nm.

[0129] Performance Testing:

[0130] After the graphite slurry is dried, powder is obtained. The particle size and resistance performance of the conductive graphite slurries prepared in all embodiments and comparative examples of the present invention are tested by a laser particle size analyzer and a four-probe resistance tester. The test results are shown in Table 1.

[0131] Table 1

[0132]

[0133]

[0134] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a conductive graphite slurry, characterized in that: The preparation method comprises: The graphite is micro-oxidized to obtain micro-oxidized conductive graphite; the micro-oxidized conductive graphite, a solvent and a dispersant are mixed and dispersed to obtain micro-oxidized conductive graphite slurry; the micro-oxidized conductive graphite slurry is nano-treated to obtain the conductive graphite slurry.

2. The preparation method according to claim 1, characterized in that The micro-oxidation treatment comprises mixing the graphite with an oxidant solution and heating the mixture for reaction; Preferably, the oxidant solution includes an oxidant, and the mass fraction of the oxidant is 0.3%-1%; Preferably, the oxidant comprises any one or a combination of at least two of peracetic acid, ammonium sulfate, potassium persulfide or sodium percarbonate; Preferably, the mass volume ratio of the graphite to the oxidant solution is 0.5 Kg / L-5 Kg / L.

3. The preparation method according to claim 2, characterized in that: The temperature of the heating reaction is 120°C-180°C; Preferably, the heating reaction time is 6h-48h.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The solvent includes an organic solvent and / or water; Preferably, the organic solvent includes any one of N-methylpyrrolidone, N,N-dimethylformamide or ethanol, or a combination of at least two thereof.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The dispersant includes any one of sodium dodecylbenzene sulfonate, polyvinyl alcohol, polyvinyl pyrrolidone, hydroxymethyl cellulose, polypropylene pyrrolidone or hydroxypropyl cellulose, or a combination of at least two thereof.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The mass ratio of the micro-oxidized conductive graphite, the organic solvent and the dispersant is (900-1100):(2500-5500):(15-25); Preferably, the method of mixing the micro-oxidized conductive graphite, the organic solvent and the dispersant comprises stirring; Preferably, the stirring speed is 950rpm-1050rpm; Preferably, the stirring time is 2h-6h.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The dispersion process is carried out in a high shear homogenizing mixer; Preferably, the flow range of the high shear homogenizer is 0.2 m 3 / h-1.5m 3 / h; Preferably, the rotation speed of the high shear homogenizer is 2000 rpm-3500 rpm.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The nano-processing method includes high-pressure microfluidics processing; Preferably, the working pressure of the high-pressure microfluidization treatment is 120MPa-150MPa; Preferably, the flow rate of the high-pressure microfluidization treatment is 100L / h-200L / h; Preferably, the operating temperature of the high-pressure microfluidization treatment is 60°C-70°C; Preferably, the number of high-pressure microfluidization treatments is 8 to 12 times; Preferably, after the nano-treatment, the average particle size of graphite in the conductive graphite slurry is 200nm-1000nm.

9. A conductive graphite slurry, characterized in that: The conductive graphite slurry is prepared by the preparation method according to any one of claims 1 to 8.

10. An application of the conductive graphite slurry as claimed in claim 9, characterized in that: The conductive graphite slurry is applied in the fields of batteries, supercapacitors, sensors or conductive coatings.

Citation Information

Patent Citations

  • Black hole liquid for printed circuit board and preparation method of black hole liquid

    CN104562115A

  • Black hole liquid and black hole technology

    CN108323036A